Control of pathogenesis in animal African trypanosomiasis: A search for answers at ILRAD, ILCA and ILRI, 1975-2018 - Black, Samuel J. (CAB International, 2020)
This book chapter describes the management of animal trypanosomiasis: (i) vector control/eradication; (ii) use of trypanocides; and (iii) use of trypanotolerant breeds of cattle. Vector control includes reducing the tsetse fly population with traps and insecticides, and in areas with a high population of trypanosome infected tsetse, animals are prophylactically administered antiparasitic drugs. To date, there is no AAT vaccine available, as discussed below. While disappointing with respect to AAT control, studies of AAT pathogenesis at ILRAD/ILRI did identify the definitive question for immunological research on AAT, namely, how do trypanosomes eliminate TD antibody responses in trypanosomiasis-susceptible mammals? In addition, the work at ILRI on the genetic basis of trypanotolerance contributed a high-density singlenucleotide polymorphism (SNP) map of the bovine genome that has intrinsic value for analysis of QTLs that control other traits, including susceptibility to other diseases.